Songs, stories, and vocabulary acquisition in preschool learners of English as a foreign language. (August 2018) - Albaladejo Albaladejo, Sara; Coyle, Yvette; de Larios, Julio Roca
Abstract: Songs and stories are regarded as popular and effective resources in the preschool classroom, but questions remain as to what effect each has on incidental vocabulary acquisition when Spanish preschool children learn English as a foreign language (EFL). This study investigates the effects that listening to stories, songs and the combination of both have on EFL vocabulary growth. One group of children (N = 17) aged two and three years old were exposed to 15 target words embedded in one story, one song, and the combination of a story and a song. Descriptive measures were employed, as well as a one-way repeated measures ANOVA test with Time and Condition as intra-subject factors; video recordings were also conducted in order to check for behavioural learning patterns. Results indicate that the Story condition yielded the highest scores, while the Song condition was the least effective. Implications are taken into consideration for content planning and incidental vocabulary learning in preschool EFL contexts.